ANALISIS KADAR AIR DAN IODIUM PADA GARAM KONSUMSI - Kurniawati, Nia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Iodized salt is salt that is included in the type of consumption salt. Before distributing this consumption salt, it is necessary to test it in accordance with the quality standards for consumption salt. In this research, the water content was tested using the gravimetric method, and the iodine level was tested using the iodometric method. The purpose of this study was to determine the water content and iodine in refined and coarse salt consumption that has or has not met the Indonesian National Standard (SNI ) 3556:2016. The resulting water content in fine salt is 0.006% and coarse salt is 0.075%. In addition, the iodine content in fine salt was 51.360 mg/kg and coarse salt was 35.4928 mg/kg. From these results it meets the quality standards for consumption salt based on Indonesian national standards.